Simulation of Forced Expiration in a Biophysical Model, With Homogeneous and Clustered Bronchoconstriction - Hedges, Kerry L. (J Biomech Eng, 2016)
One limitation of forced spirometry is that it integrates the contribution of the complex and dynamic behavior of all of the airways and tissue of the lung into a single exhaling unit, hence, it is not clear how spirometric measures are affected by local changes to the airways or tissue such as the presence of “ventilation defects.” Here, we adapt a wave-speed limitation model to a spatially distributed and anatomically based airway tree that is embedded within a deformable parenchyma, to simulate forced expiration in 1 s (FEV(1)). This provides a model that can be used to assess the consequence of imposed constrictions on FEV(1). We first show how the model can be parameterized to represent imaging and forced spirometry data from nonasthmatic healthy young adults. We then compare the effect of homogeneous and clustered bronchoconstriction on FEV(1) in six subject-specific models (three male and three female). The model highlights potential sources of normal subject variability in response to agonist challenge, including the interaction between sites of airway constriction and sites of flow limitation at baseline. The results support earlier studies which proposed that the significant constriction of nondefect airways must be present in order to match to clinical measurements of lung function.